RGO/Nylon-6 Composite Mat with Unique Structural Features and Electrical Properties Obtained from Electrospinning and Hydrothermal Process - Pant, Hem Raj; Pant, Bishweshwar; Park, Chan Hee; Kim, Han Joo; Lee, Dong Su; Tijing, Leonard D.; Hwang, Bo Sang; Kim, Hak Yong; Kim, Cheol Sang (KOREAN FIBER SOC, 2013)
In this work, the reduced graphene oxide (RGO) sheets were effectively uploaded through nylon-6 fibers using combined process of electrospinning and hydrothermal treatment. Good dispersion of graphene oxide (GO) with nylon-6 solution could allow to upload GO sheets through nylon-6 fibers and facilitate the formation of spider-wave-like nano-nets during electrospinning. GO sheets present on/into nylon-6 spider-wave-like nano-nets were further reduced to RGO using hydrothermal treatment. The impregnated GO sheets into nylon-6 nanofibers and their reduction during hydrothermal treatment were confirmed by FE-SEM, TEM, FT-IR and Raman spectra. The electrical characteristics of pristine nylon-6, GO/nylon-6 and RGO/nylon-6 nanofibers were investigated and it was found that RGO/nylon-6 composite mat had better electrical conductivity than others. The formation of spider-wave-like nano-nets as well as indirect route of incorporation of RGO sheets on electrospun nylon-6 mat may open a new direction for future graphene/polymer electronics.
Keywords: FIBER MORPHOLOGY; NANOFIBERS; NYLON-6; CARBON; NANOPARTICLES; FABRICATION